A study to evaluate pregnancy with maternal heart disease: a prospective observational study at a tertiary care centre in India - Goel, Khushboo; Tambe, Sanjaykumar G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Prevalence of heart disease in pregnancy vary from 0.3-3.5%. Normal pregnancy is associated with physiological cardiovascular changes. These changes may unmask underlying cardiac disease in normal women and increase morbidity and mortality in women with heart disease. Heart disease in pregnancy is an important cause of maternal mortality in India. The aim of this study was to evaluate the maternal and neonatal outcome of pregnancy with heart disease. Methods: A prospective observational study was conducted at Sassoon General Hospital, Pune, India. 75 patients who fulfilled the inclusion criteria were studied. Maternal and neonatal outcome were analyzed. Results: Maternal heart disease was classified into congenital (36%) and acquired (64%). In acquired variety, rheumatic heart disease was most commonly seen. In congenital, ASD was most common. We divided the cases into two groups based on their NYHA status, low risk group had 74.67% patients and high risk group had 25.33% patients. The most common antenatal complication was PROM (41.3%). There was statistically significant association between ICU admission and high-risk group. The most common neonatal complications were IUGR and prematurity. Maternal mortality rate in the study group was 6.6%. Conclusions: The perinatal outcome of heart disease in pregnancy is more dependent on the severity of symptoms rather than the duration and type of heart disease. Multidisciplinary evaluation is necessary. Suboptimal optimization of the heart condition in the antenatal period and delayed referral were the major risk factor for maternal mortality.